Impact of colonization pressure on acquisition of extended-spectrum β-lactamase-producing Enterobacterales and meticillin-resistant Staphylococcus aureus in two intensive care units: a 19-year retrospective surveillance. Issue 1 (May 2020) - Jolivet, S.; Lolom, I.; Bailly, S.; Bouadma, L.; Lortat-Jacob, B.; Montravers, P.; Armand-Lefevre, L.; Timsit, J-F.; Lucet, J-C.
Summary: Background: Colonization pressure is a risk factor for intensive care unit (ICU)-acquired multi-drug-resistant organisms (MDROs). Aim: To measure the long-term respective impact of colonization pressure on ICU-acquired extended-spectrum β-lactamase-producing Enterobacterales (ESBL-PE) and meticillin-resistant Staphylococcus aureus (MRSA). Methods: All patients admitted to two ICUs (medical and surgical) between January 1997 and December 2015 were included in this retrospective observational study. Rectal and nasal surveillance cultures were obtained at admission and weekly thereafter. Contact precautions were applied for colonized or infected patients. Colonization pressure was defined as the ratio of the number of MDRO-positive patient-days (PDs) of each MDRO to the total number of PDs. Single-level negative binomial regression models were used to evaluate the incidence of weekly MDRO acquisition. Findings: Among the 23, 423 patients included, 2327 (10.0%) and 1422 (6.1%) were colonized with ESBL-PE and MRSA, respectively, including 660 (2.8%) and 351 (1.5%) acquisitions. ESBL-PE acquisition increased from 0.51/1000 patient-exposed days (PEDs) in 1997 to 6.06/1000 PEDs in 2015 ( P <0.001). In contrast, MRSA acquisition decreased steadily from 3.75 to 0.08/1000 PEDs ( P <0.001). Controlling for period-level covariates, colonization pressure in the previous week was associated with MDRO acquisition for ESBL-PE ( P <0.001 and P =0.04 for medical and surgical ICU, respectively), but not for MRSA ( P =0.34 and P =0.37 for medical and surgical ICU, respectively). The increase in colonization pressure was significant above 100/1000 PDs for ESBL-PE. Conclusion: Colonization pressure contributed to the increasing incidence of ESBL-PE but not MRSA. This study suggests that preventive control measures should be customized to MDROs.